Elemental home: a video game to explore chemistry in everyday life - Juárez González, Pedro; Cano-Iglesias, María José; Cebrián-Robles, Daniel; Franco-Mariscal, Antonio Joaquín (ACS, 2025)
This study presents and analyzes Elemental Home, a video game designed for teaching chemistry, with a specific focus on chemical elements in everyday life. Set inside a house, the video game situates learning in an everyday context, challenging players to identify chemical elements in household objects while reflecting on their environmental impact. This paper evaluates the learning potential and user experience of Elemental Home, based on the participation of 18 Spanish preservice chemistry teachers and 18 ninth-grade students. Learning in both groups was evaluated using data collected from the video game’s database, while usability and user satisfaction were assessed through a questionnaire. Additionally, ninth-grade students completed a pretest and post-test to measure their understanding of associations between chemical elements and everyday objects. Both students and preservice teachers surpassed 70% accuracy in element−object associations at level 1 (14/18 for students and 10/ 18 for preservice teachers), although students required more attempts on average to reach this level (4.22 compared to 2.28 attempts). While students progressed only to level 2, preservice teachers advanced as far as level 4. Additionally, Elemental Home delivers a positive user experience for preservice teachers (usability: 77.35/100; satisfaction: 75.00/100) and is regarded as moderately engaging by students (usability: 64.44/100; satisfaction: 64.50/100). Results emphasize the potential of video games in chemical education, demonstrating how the combination of game-based learning, contextualization, and interactive elements can significantly transform traditional teaching and learning approaches in chemistry.
Keywords: Química - Estudio y enseñanza; First-Year Undergraduate; General, High School; Introductory Chemistry; Physical Chemistry; Humor; Puzzles; Games, Periodicity; Periodic Table; Student-Centered Learning